Revisiting the Functions of Curriculum Theory: A Foundational Ground for the Development of Procedural Model to Determine the Null Curriculum - Cahapay, Michael Bobias (Indonesian Journal of Curriculum and Educational Technology Studies, 2020)
A discussion of the functions of curriculum theory appears to be mostly overlooked in the scholarly works that endeavor to develop models in certain curriculum areas. This essay article revisits the functions of curriculum theory as a foundational ground for the development of a procedural model to determine the null curriculum. I first discuss in this article the functions of curriculum theory such as description, explanation, prediction, and guidance. Then, specifically under the guidance function, I trace the task of model development in Curriculum Studies. Finally, I relate towards the end of this article the current need to develop a procedural model to determine the null curriculum. Abstrak Diskusi mengenai fungsi teori kurikulum tampak lebih banyak diperhatikan di dalam dunia akademik yang berupaya mengembangkan model-model dalam bidang-bidang kurikulum tertentu. Artikel ini bertujuan untuk meninjau kembali fungsi dari teori kurikulum sebagai dasar yang sifatnya fondasional dalam pengembangan model prosedural untuk memastikan rumusan Null Curriculum. Pertama saya mendiskusikan mengenai fungsi teori kurikulum, misalnya fungsi mendeskripsikan, menjelaskan, memprediksi, dan membimbing. Kemudian secara lebih spesifik mengacu pada fungsi pembimbingan dari kurikulum saya menelusuri tugas model pengembangan dalam Kajian Kurikulum. Terakhir, saya mengaitkannya dengan kebutuhan untuk mengembangkan model prosedural untuk memantapkan rumusan Null Curriculum.